'Dignity and respect': An example of service user leadership and co‐production in mental health research. (26th September 2019) - Faulkner, Alison; Carr, Sarah; Gould, Dorothy; Khisa, Christine; Hafford‐Letchfield, Trish; Cohen, Rachel; Megele, Claudia; Holley, Jessica
Abstract: This paper explores the methodological aspects of a user‐led study investigating mental health service user experiences of targeted violence and abuse (often called 'hate crime'). 'Keeping Control' was a 16‐month qualitative study, undertaken in the context of adult safeguarding reforms in England. By collecting data on service user concepts and experiences, the research sought to address a gap in research and practice knowledge relating to targeted violence, abuse and hostility against people with mental health problems. In this paper, we discuss the significance of the design and methodology used for this study, with a particular focus on the interviews with service users. The research was both user‐led and carried out in collaboration with practitioners and academics, a form of research co‐production. Our aim is to inform researchers, practitioners and policymakers about the value of user leadership in co‐productive research with practitioners, particularly for a highly sensitive and potentially distressing topic.